PENCOCOKAN GAMBAR SIDIK JARI DENGAN KAMERA HANDPHONE MENGGUNAKAN METODE RANSAC DAN TRANSFORMASI AFFINE BERBASIS ANDROID - Sajati, Haruno; Nughraheny, Dwi; Suwarso, Nova Adi (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2017)
Fingerprints occur due to stroke differences. These stroke differences have occurred at a time when humans are still fetal form. A normal fingerprint pattern is formed of lines and spaces. These lines are called ridges whereas the spaces between these lines are called valleys. To make an introduction to the fingerprint image requires a variety of support tools. Starting from a fingerprint machine, a smartphone that has a fingerprint sensor and much more. In this research, the acquisition of image is done by grayscaling, histogram equalization, gabor filter, binary, thinning, 8 neighbors, matching.The result of making android application with the method that has been described to show unfavorable results seen from the calculation of the accuracy of 63%. Based on testing the specs android OS devices, this application can run on android with OS 4.4.2 specification kitkat.Fingerprints occur due to stroke differences. These stroke differences have occurred at a time when humans are still fetal form. A normal fingerprint pattern is formed of lines and spaces. These lines are called ridges whereas the spaces between these lines are called valleys. To make an introduction to the fingerprint image requires a variety of support tools. Starting from a fingerprint machine, a smartphone that has a fingerprint sensor and much more. In this research, the acquisition of image is done by grayscaling, histogram equalization, gabor filter, binary, thinning, 8 neighbors, matching.The result of making android application with the method that has been described to show unfavorable results seen from the calculation of the accuracy of 63%. Based on testing the specs android OS devices, this application can run on android with OS 4.4.2 specification kitkat. Keywords : OCR Fingerprint, Fingerprint recognition, Minutiae based matching, Fingerprint image processing.